Why Voting Does Not Imply Consenting - Ramelet, Laetitia (Frontiers in Political Science, 2020)
One of the reasons that elections have come to be so widely valued across the globe lies in their perceived ability to increase citizens' consent to be governed by their representatives. Yet, inversely, one may ask what election results tell us about citizens' consent. For instance, to what extent can election winners be assumed to enjoy citizens' consent? Does voting automatically imply consent to the outcome of the election? What does abstention mean? This paper addresses the question of what election results reveal about citizens' consent, from an empirically informed normative perspective. The question is of political importance, because the connection between voting and consenting is often exploited for political gain, and because representative institutions are now being increasingly questioned by citizens themselves. I plead for caution in any endeavor to interpret election results in terms of consent, and I argue that it would be wrong to assume, by default, that voters intend their vote to express consent. Rather, voters' motives can only be ascertained by asking voters about them, and cannot be deduced from their sole act of voting. In addition, much variation is to be expected regarding what is being consented to, and to what degree.